THE ASYMMETRIC RESILIENCE OF GREEN BONDS: RECONCILING GEOPOLITICAL VULNERABILITY WITH CORPORATE VALUE CREATION (American Journal of Business Management, Economics and Banking, 2026)
The rapid expansion of green bonds positions sustainable finance at the core of climate mitigation strategies. However, empirical evidence on their crisis resilience and corporate value effects remains contradictory. This study synthesizes 73 peer-reviewed articles using meta-analytical methods (random-effects models, FAT-PET, PEESE) to resolve these discrepancies. We propose and test the Asymmetric Shock Resilience Hypothesis: green bonds exhibit diametrically opposite behaviors depending on shock origin. During financial or health crises (e.g., COVID-19), they act as safe havens, shielded by concentrated institutional ownership (Herfindahl-Hirschman Index = 0.28 vs. 0.15 for conventional bonds). Conversely, during geopolitical risk (GPR) episodes (e.g., Ukraine war), green bonds demonstrate severe vulnerability, with negative return shocks absent in conventional markets. At the corporate level, global average financial effects are negligible (μ = -0.005, p = 0.225), but this masks strong moderation: developed markets exhibit a significant "greenium" (lower cost of capital), while emerging markets (e.g., China) show negative post-issuance effects (μ = -0.041) due to prohibitive certification costs. We conclude that the greenium is not a static advantage but a contingent premium dependent on systemic stability and market maturity.